Adenosine A2a receptor stimulation prevents proteinuria in diabetic rats by promoting an anti‐inflammatory phenotype without affecting oxidative stress. (6th May 2015) - Persson, P.; Friederich‐Persson, M.; Fasching, A.; Hansell, P.; Inagi, R.; Palm, F.
Abstract Aim Diabetic patients are at increased risk for kidney disease. There is presently no clinical treatment available that effectively protects kidney function in diabetics. This study investigates whether chronic stimulation of the adenosine A2a receptor (A2aAR) protects kidney function in insulinopenic diabetic rats. Methods Streptozotocin‐induced diabetic rats and corresponding controls were chronically treated with the adenosine A2aAR agonist CGS21680 throughout the four‐week diabetes duration. Kidney function was thereafter investigated, and urine and plasma samples were collected for analysis of protein, oxidative stress and inflammatory markers. Results Glomerular filtration rate, renal blood flow, filtration fraction and diabetes‐induced kidney hypoxia were all unaffected by chronic A2aAR stimulation. Furthermore, diabetic rats had increased oxidative stress, which was further increased by chronic A2aAR stimulation. However, the 10‐fold increased urinary protein excretion observed in the diabetic rats was completely prevented by chronic A2aAR stimulation. These beneficial effects were accompanied by reduced levels of the pro‐inflammatory TNF‐α and increased levels of the anti‐inflammatory IL‐10 as well as decreased infiltration of macrophages, glomerular damage and basement membrane thickness. Conclusion Chronic A2aAR stimulation prevents proteinuria and glomerular damage in experimental diabetes via an anti‐inflammatory mechanism independent of oxidative stress and kidney hypoxia.